2006
DOI: 10.2460/ajvr.67.11.1921
|View full text |Cite
|
Sign up to set email alerts
|

Expression of neural markers on bone marrow–derived canine mesenchymal stem cells

Abstract: Canine bone marrow-derived mononuclear cells yielded an apparently homogeneous population of MSCs after expansion in culture. Expanded canine MSCs constitutively expressed neuron or astrocyte specific proteins. Furthermore, increases of intracellular cAMP concentrations induced increased expression of GFAP on canine MSCs, which suggests that these cells may have the capacity to respond to external signals. Canine MSCs may hold therapeutic potential for treatment of dogs with neurologic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
51
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 52 publications
9
51
0
3
Order By: Relevance
“…In this study, adherent stromal cells isolated from the bone marrow and adipose tissue were used as cBMMSCs and cADMSCs [10,29]. A previous study by Zuk et al demonstrated that plastic-adherent cells isolated from human adipose tissue, labeled as MSCs, also contained non-MSC population [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, adherent stromal cells isolated from the bone marrow and adipose tissue were used as cBMMSCs and cADMSCs [10,29]. A previous study by Zuk et al demonstrated that plastic-adherent cells isolated from human adipose tissue, labeled as MSCs, also contained non-MSC population [40].…”
Section: Discussionmentioning
confidence: 99%
“…cBMMSCs were isolated and cultured according to a previous method with minor modifications [10]. Briefly, the bone marrow collected was dissociated, and then resuspended with a pipette.…”
Section: Animalsmentioning
confidence: 99%
“…In order to assess the maturation of differentiated cells, III-tubulin and NeuN were used as early and mature neuronal markers, respectively. The cross-reactivity of these primary antibodies to canine cells has been confirmed by our preliminary experiment and previous study [7]. Brain slices were washed three times in PBS and permeabilized in 0.4% Triton X-100 in PBS for 30 min at 25C.…”
Section: Preparation Of Canine Bmscs and Fibroblastsmentioning
confidence: 92%
“…Mononucleated cells were isolated on a Ficoll (Ficoll-Paque, StemCell Technologies, Vancouver, Canada) density gradient, washed in PBS, and suspended in culture medium consisting of DMEM (1g/l glucose) supplemented with 10% fetal bovine serum (FBS) and antibiotics (100 U/ml penicillin G, 100 g/ml streptomycin sulfate, and 0.25 g/ml amphotericin B). Cell surface marker profiles, growth kinetics, and differentiation properties of isolated canine BMSCs have been described in our previous studies [6][7][8]. Canine skinderived third passage fibroblasts (Coriell Institute for Medical Research) were used for comparative purposes.…”
Section: Preparation Of Canine Bmscs and Fibroblastsmentioning
confidence: 99%
“…33 Another study for canine BMCs has shown that mesenchymal stem cells (MSCs) were obtained after canine BMMNC culture with DMEM medium supplemented with 20% FBS and the cell surface marker expression of these cells were comparable to those reported in human and rodent MSCs. 34 Analysis by flow cytometry revealed that these cells were positive for CD90 and MHC-I and negative for CD34 and CD45, indicating that cells with hematopoietic origin were excluded during cell expansion process under this culture condition. 34 BMCs represent an alternative cell source for tissue engineering of vascular grafts.…”
Section: Discussionmentioning
confidence: 99%